The Decline of University Sports in India: Causes and Retention Measures - Wani, Iftikhar Ahmad; Faridi, Merajuddin (Journal of Sports Research, 2022)
The objective of this study was to determine the causes of the decline of sports in the universities of India. A structured questionnaire was used to collect the data from India’s hundred-year-old three central universities. The subjects for this study were the administrators, coaches, and players of the University Sports Boards. A multi-stage sampling technique was adopted for this study. At first, the three central universities, Aligarh Muslim University, Banaras Hindu University, and Jamia Millia Islamia, were selected purposively based on uniformity. Three hundred thirteen subjects, including 39 administrators, 29 coaches, and 245 players, were randomly selected from the three universities. RIDIT analysis followed by the Kruskal Wallis test was used to analyze the data and hypothesis. The study results unveiled that the effectiveness of sports in the universities of India has declined. There is no strategic planning with clear and attainable objectives for the management of sports in the universities of India. The study displayed the causes of its decline and suggested retention measures. Further research is needed to explore sports in the universities of India.